TEACHING ESP USING PROJECT-BASED LEARNING AT TECHNICAL UNIVERSITIES - Hural, Oksana (European Science, 2024)
This article discusses the general characteristics of the project-based approach to learning foreign languages. The possibility of interactive foreign language teaching in universities based on the model of independent student project work is studied. Con